Characteristics and trajectory of patients with pediatric acute respiratory distress syndrome. Issue 4 (3rd February 2020) - Wong, Judith Ju‐Ming; Tan, Herng Lee; Lee, Siew Wah; Chang, Kenneth Tou En; Mok, Yee Hui; Lee, Jan Hau
Abstract: Objective: This study delineates the disease trajectory of patients with pediatric acute respiratory distress syndrome (PARDS) defined by the Pediatric Acute Lung Injury Consensus Conference (PALICC) definition, and evaluates the impact of comorbidities on outcomes. Methods: This prospective study over November 2017‐October 2019 was conducted in a single‐center multidisciplinary pediatric intensive care unit (PICU) and included patients <21years of age with PARDS. Clinical history of those requiring mechanical ventilation for <3 days was interrogated and cases in which the diagnosis of PARDS were unlikely, identified. The impact of chronic comorbidities on clinical outcomes, in particular, pulmonary disease and immunosuppression, were analyzed. Results: Eighty‐five of 1272 PICU admissions (6.7%) met the criteria for PARDS and were included. Median age and oxygenation indexes were 2.8 (0.6, 8.3) years and 10.6 (7.6, 15.4), respectively. Overall mortality was 12 out of 85 (14.1%). Despite fulfilling criteria in 6/85 (7.1%), hypoxemia contributed by bronchospasm, mucus plugging, fluid overload, and atelectasis was quickly reversible and PARDS was unlikely in these patients. Comorbidities (57/85 [67.1%]) were not associated with worsened outcomes. However, pre‐existing pulmonary disease and immunosuppression were associated with severe PARDS (12/20 [60.0%] vs 19/65 [29.2%]; P  = .017), extracorporeal membrane oxygenation use (5/20 [25.0%] vs 3/65 [4.6%]; P  = .016) and reduced ventilator free days (VFD) (15 [0, 19] vs 21 [6, 23]; P  = .039), compared with those without them. Conclusion: A small percentage of children fulfilling the PALICC definition had quickly reversible hypoxemia with likely alternate pathophysiology to PARDS. Patients with pulmonary comorbidities and immunosuppression had a more severe course of PARDS compared with others.